Profitabilitas, Leverage, Ukuran Perusahaan, dan Kinerja Lingkungan yang dimoderasi Profil Perusahaan pada Pengungkapan CSR - Padlah Riyadi; Novita W. Respati; Ayu Octaviani (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to determine and analyze the effect of profitability, leverage, firm size and environmental performance moderated by company profile variable on the CSR disclosures of companies listed on the IDX in 2014-2019. Based on purposive sampling, there were 12 companies according to the research criteria multiplied by the number of 6 years of observation, 72 data were processed and analyzed using multiple linear regression. Partial testing shows that only leverage significantly effects CSR disclosure, while profitability, firm size, enviromental performance and company profile do not significantly effect CSR Disclosure. From direct testing, it was found that there was no relationship between the company profile and CSR disclosure so that the moderation test did not continue.